(untitled) (Texas Journal of Philology, Culture and History, 2022)
Among the many historical places in the Jizzakh region of the Republic of Uzbekistan, this monument is a clear example of how many great scholars and saints there were in our lands in the distant past. Our priority is to preserve this landmark in the form it came down to us and pass it on to future generations by making the public aware of this place.